Cultivation and sequencing-free protocol for Serratia marcescens detection and typing - Alessandro Alvaro; Aurora Piazza; Stella Papaleo; Matteo Perini; Ajay Ratan Pasala; Simona Panelli; Tiago Nardi; Riccardo Nodari; Lodovico Sterzi; Cristina Pagani; Cristina Merla; Daniele Castelli; et al. (iScience, 2024)
Summary: Serratia marcescens is an opportunistic pathogen that survives in inhospitable environments causing large outbreaks, particularly in neonatal intensive care units (NICUs). Genomic studies revealed that most S. marcescens nosocomial infections are caused by a specific clone (here “Infectious clone”). Whole genome sequencing (WGS) is the only portable method able to identify this clone, but it requires days to obtain results. We present a cultivation-free hypervariable-locus melting typing (HLMT) protocol for the fast detection and typing of S. marcescens, with 100% detection capability on mixed samples and a limit of detection that can reach the 10 genome copies. The protocol was able to identify the S. marcescens infectious clone with 97% specificity and 96% sensitivity when compared to WGS, yielding typing results portable among laboratories. The protocol is a cost and time saving method for S. marcescens detection and typing for large environmental/clinical surveillance screenings, also in low-middle income countries.